(Non-)translational medicine: targeting bacterial RNA - Dinan, Adam M.; Loftus, Brendan J. (Frontiers in Genetics, 2013)
The rise and spread of antibiotic resistance is among the most severe challenges facing modern medicine. Despite this fact, attempts to develop novel classes of antibiotic have been largely unsuccessful. The traditional mechanisms by which antibiotics work are subject to relatively rapid bacterial resistance via mutation, and hence have a limited period of efficacy. One promising strategy to ameliorate this problem is to shift from the use of chemical compounds targeting protein structures and processes to a new era of RNA-based therapeutics. RNA-mediated regulation (riboregulation) has evolved naturally in bacteria and is therefore a highly efficient means by which gene expression can be manipulated. Here, we describe recent advances toward the development of effective anti-bacterial therapies, which operate through various strategies centered on RNA.